The Tiger's Apprentice - Yep, Laurence (New York : HarperCollins, 2003)
A tiger, a monkey, a dragon, and a twelve-year-old Chinese American boy fight to keep a magic talisman out of the hands of an enemy who would use its power to destroy the world.
Keywords: Magic -- Fiction; Chinese Americans -- Fiction; Orphans -- Fiction; San Francisco (Calif.) -- Fiction